Stab Injury with Tailoring Scissor Causing Inferior Gluteal Artery Pseudo Aneurysm: a Rare Case Report - Haseen, MA; Mahmud, AA; Arshad, M; Haneef-Beg, M (International Journal of Medical Toxicology and Forensic Medicine, 2015)
Background: Gluteal artery pseudo aneurysm (GAP) is a rare entity, as gluteal arteries are well protected under muscles and fat of gluteal region. Gluteal artery aneurysms constitute less than 1% of all aneurysms and most of them are pseudo aneurysms. The common etiologies of GAP areblunt or penetrating trauma to gluteal region, infection, fractures of the pelvis or iatrogenic injury during surgical procedures on the pelvis or hips to intramuscular injection. The usual presentation is a pulsatile gluteal mass often confused with a gluteal abscess presenting 1-2 months after injury. However, at times it can cause symptoms due to compression of pelvic structures. Case Report: Our patient was a young boy who had injury to his right gluteal region with a tailoring scissor during a scuffle. He presented to casualty in shock with packing of wound done outside. After resuscitation his Computed tomographic angiography (CT angiography) revealed a psuedoanuerysm of inferior gluteal artery. He was immediately taken up for surgery a transperitoneal ligation of internal iliac artery of the involved side was done along with exploration of the gluteal wound. Conclusion: These patients of Gluteal artery aneurysms can be managed with both open and endovascular techniques. Our patient was unique in the respect that no GAP has been reported after stab injury with a tailoring scissor and ours is first case report in English literature .We want that the surgeons should keep in mind the possibility of GAP while dealing with even trivial injuries of gluteal region.